Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2fo01144a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different enzymatic hydrolysates of konjac glucomannan on gut flora and constipation in rats

Abstract: This study aimed to compare the effects of different hydrolysates (named GKOS and MKOS) on constipated rats, which were degraded to obtain from konjac glucomannan by β-glucanase and β-mannanase, respectively....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…52 Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. 53,54 Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. 25,26 FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. 53,54 Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. 25,26 FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Gut microbiota are closely related to host health and influenced by nutritional intake and lifestyle . Previous studies have shown that prebiotics can reduce constipation by regulating the microbial composition of the intestinal tract. , Both polyphenols and polysaccharides extracted from FBT have been proven to regulate intestinal flora and maintain host health. , FTE is extracted from FBT infusion, which has been proven to promote the colonization of beneficial bacteria such as Roseburia and Lactobacillus . Here, the 16S rRNA gene amplicon sequencing technology was used to analyze gut microbial changes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucomannan and its hydrolysate oligosaccharides can selectively regulate the number and distribution of beneficial intestinal microflora (lactic acid bacteria, bifidobacteria, cecal anaerobes, etc. ), reduce the incidence of colon cancer, and have excellent prebiotic effects [ 34 , 35 , 36 , 37 ]. In the near future, related products with glucomannan as the main raw material, such as some medical functional foods, will gradually enter the market and become known to the public.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that konjac glucomannan could alleviate constipation by increasing SCFA levels, which were crucial for maintaining the microecological balance of the intestine. 69 SCFAs could lower the gut pH, which may inhibit the growth of harmful bacteria and boost salt and hydration absorption in the colon. 70 Furthermore, studies reported that SCFAs could promote the growth of colon cells.…”
Section: Food and Function Papermentioning
confidence: 99%